Push and Pull Motivations on Halal Tourism - Faulina, Faulina; Siregar, Efni; Novita, Vivianti; Arimbi, Siti (Graduate School, Universitas Brawijaya, 2020)
The purpose of this study was to examine empirically the causal relationships among push and pull travel motivations, destination image, and tourists' travel satisfaction on halal tourism. The research conceptual framework and hypotheses were constructed, based on previous theoretical and empirical studies. A questionnaire survey was conducted with 200 respondents to collect the primary data. Multiple regression and Path Analyses were conducted to test the research hypotheses. As a result, push and pull factors had directly positive influences on tourist's travel satisfaction. Besides, the results also showed that push and pull factors were slightly indirect effect tourist's travel satisfaction through the halal destination image. Consequently, local government and business organizations working in the tourism sector should pay attention to the essential roles of push and pull factors. To attract more potential visitors and improve their satisfaction, enhance their perceived on halal destination image by doing the facility improvement and marketing activities are the compulsory actions.Keywords: destination image, halal tourism, motivation, push, and pull, travel satisfaction.